THE IMPACT OF TALENT MANAGEMENT, ENTREPRENEURIAL ORIENTATION AND ORGANIZATIONAL LEARNING ON ORGANIZATIONAL PERFORMANCE AMID AND POST- COVID-19 PANDEMIC: THE CONCEPTUAL FRAMEWORK FOR MEDIATING ROLE OF ORGANIZATIONAL LEARNING - OTHMAN, MOHAMAD ROSNI; SAADON, MOHD SAIFUL IZWAAN; ALLEIMOUN, AUDEH (Journal of Maritime Logistics, 2022)
In today’s hypercompetitive business environment amid the ongoing COVID-19 pandemic, there is an urgent need for organizations to maximize their flexibility and capabilities to be able to operate in continuously and rapidly changing markets. Organizations must embrace effective methods and practices to not only cope with shifts in their corresponding markets but to recreate their markets and identify new opportunities. This research seeks to contribute to the expanding body of literature exploring crucial organizational performance determinants amid and post-COVID-19 eras. The study synthesizes the key research findings in the context of talent management, entrepreneurial orientation, and organizational learning to propose a conceptual model depicting these factors as key concepts to enhance organizational performance in the current turbulent business world. It also attempts to synthesize the knowledge from the aforementioned fields to better understand of the potential mediating role of organizational learning.